Role of Radiation Therapy for Renal Tumors - Parashar, Bhupesh; Patro, Kanhu Charan; Smith, Michael; Arora, Shruthi; Nori, Dattatreyudu; Wernicke, A. Gabriella (Seminars in Interventional Radiology, 2014)
Renal cell carcinoma (RCC) is an aggressive malignancy that carries a poor prognosis, especially in patients presenting with advanced stage. Primary treatment for localized RCC is surgical resection however, a significant number of patients still develop locoregional and distant metastasis after curative resection. In metastatic disease, radiation therapy (RT) has been used for palliation routinely for brain and other extracranial lesions with respectable response rates. However, RT for primary RCC has questionable benefit. In this article, the authors discuss the evidence with regards to the role of RT in primary RCC either as a primary treatment, adjuvant treatment, or preoperatively to improve resection outcomes. In addition, novel RT techniques such as stereotactic body radiation therapy and its use in RCC management are also addressed. Finally, the authors discuss the techniques and doses of RT for primary RCC.
Keywords: renal; radiation; stereotactic; intensity-modulated radiation therapy; role